Phytochemical And Antibacterial Effect Of Dry Fruits Of Garcinia Gummi-Gutta (L.) Roxb - Juliya V Devasia; Pinkie Cherian (International Journal of Pharma and Bio Sciences, 2020)
India is a rich repository of medicinal plants. Pathogenic microorganisms cause life threatening infections and its frequency may increase day by day and it increases morbidity and mortality in immune compromised patients. Among the different species of Garcinia, G. gummi-gutta is the most widely distributed Garcinia species in Kerala, south India. Garcinia gummi-gutta, popularly known as Malabar tamarind or kodampuli is a tropical fruit tree species of high potential and fruit is used as culinary spice, preservatives and also as a source of several nutraceutical products. The study was designed with an objective to evaluate the phytochemicals and antibacterial properties of Garcinia gummigutta fruit extracts. The preliminary phytochemical screening tests may be useful in the detection of the bioactive principles and subsequently may lead to the drug discovery and development. The preliminary phytochemical screening was carried out using standard methods. The dried fruits of Garcinia gummi-gutta were collected, dried, and extracted using hexane, ethyl acetate, chloroform, acetone and hydro alcohol solvents. The extracts of Garcinia gummigutta were tested positive for Carbohydrate, Terpenoids, Amino acids, Tannins, Cardiac glycosides, Flavonoids, Phlobatanins, Steroids, Phenolic compound and saponin. The prepared fruit rind extracts were examined to evaluate the antibacterial activity against both gram-positive (Bacillus cereus, Staphylococcus aureus) and negative bacteria (Escherichia coli) using agar disc diffusion assay. The zone of inhibition was measured.. The hydro alcohol extract is found to be most effective against the microorganism Hence, Garcinia gummigutta can be used to discover bioactive natural products that may serve as leads in the development of nutraceuticals or therapeutical agents to prevent several diseases.